Basic sales skills--business to business (The Certified sales professional's library., 1995)
Salespeople who close the sales that count usually rely on basic sales skills. And as a new sales professional in today's increasingly competitive market, you are looking for information to help you master the basic skills and become more effective in closing sales. Ideal for sales professionals just entering the field, Basic Sales Skills covers all of the basic skills and coaching techniques you need to become a consistently productive, effective sales professional. Whether you are just starting out in sales or have a few years of experience, brushing up on and mastering the fundamentals can help you shift your career into high gear.